2015
DOI: 10.21608/jacb.2015.48479
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Genetic Variability and Divergence in Some Selected Lines of Pearl Millet

Abstract: The objective of this study was to estimate the genetic variability , heritability , genotypic and phenotypic coefficients of variations , genetic advance , range , genotypic and phenotypic variances and to study the genetic divergence by using multivariate analysis for yield and yield components in forty selected lines of pearl millet during 2012 and 2013 summer seasons at Sakha Agriculture Research Station. Analysis of variance manifested highly significant differences among all selected lines for all the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Evaluation of genotypes from these clusters for per se performance and specific combining ability will identify the most promising lines and enable their utilisation as pollinators in developing of hybrids. Similar results were also provided by Drabo et al, 2013;Ghazy et al, 2015;Kiprotich et al, 2015;Nehra et al, 2016;Ton et al, 2022. Cluster III had the maximum mean grain yield per plant (26.48 g), dry fodder yield per plant (56.33 g),1000-seed weight (9.89 g), and plant height (162.88 cm). Cluster VI had the highest grain Mg content (2365.29 mg kg -1 ) and number of productive tillers per plant (2.90), and the lowest days to 50% flowering (60), panicle length (17.70 cm), plant height (126.50 cm), dry fodder yield per plant (18.12 g), 1000-seed weight (8.31 g), and grain yield per plant (8.31 g).…”
Section: Resultssupporting
confidence: 87%
“…Evaluation of genotypes from these clusters for per se performance and specific combining ability will identify the most promising lines and enable their utilisation as pollinators in developing of hybrids. Similar results were also provided by Drabo et al, 2013;Ghazy et al, 2015;Kiprotich et al, 2015;Nehra et al, 2016;Ton et al, 2022. Cluster III had the maximum mean grain yield per plant (26.48 g), dry fodder yield per plant (56.33 g),1000-seed weight (9.89 g), and plant height (162.88 cm). Cluster VI had the highest grain Mg content (2365.29 mg kg -1 ) and number of productive tillers per plant (2.90), and the lowest days to 50% flowering (60), panicle length (17.70 cm), plant height (126.50 cm), dry fodder yield per plant (18.12 g), 1000-seed weight (8.31 g), and grain yield per plant (8.31 g).…”
Section: Resultssupporting
confidence: 87%
“…The knowledge of the nature and magnitude of genetic variability for a heritable trait is essential to exploit the yield contributing trait. Assessment of genetic diversity distance via D 2 analysis, between two genotypes, will help to choose better parents for hybridization (Ghazy et al, 2015;Kiprotich et al, 2015;Sharma et al, 2020). Intercrossing between genetically divergent genotypes is expected to produce superior hybrids and desirable recombinants.…”
Section: Introductionmentioning
confidence: 99%
“…The degree and nature to which yield is related with other traits allows breeders to foresee the relative impact of different traits on yield improvement that allowing them to choose the traits that are desirable and crucial to achieving improvement. Berwal and Khairwal (1997) and Ghazy et al (2015) studied the genetic variation for forty genotypes of pearl millet and observed a significance difference in height of plant, no. of tillers, stem diameter, fresh, dry leaf/stem ratio and total fresh and dry forage yield across three cuts and over two seasons.…”
Section: Introductionmentioning
confidence: 99%